(untitled) (Acta Scientiarum. Biological Sciences, 2018)
Tissue culture techniques have been employed for orchid mass propagation by means of the morphogenetic route of protocorm like-bodies (PLBs). This study aimed to analyze and compare Indole-acetic acid (IAA) and sugar endogenous levels in protocorm-like bodies (PLBs) induction and development in Cattleya tigrina, in order to better understand this process and to optimize micropropagation procedure protocols. Leaves grown on MS (Murashige and Skoog) culture medium, suplemented with 9 Î¼M TDZ for PLBs induction and development were collected after 0, 2, 7, 14, 30, 60 and 100 days of cultivation, for further analysis. Increase of IAA and reduction of sugar levels are strongly related to morphogenetic response, that is, PLBs formation over the preexisting ones and leaf primordia formation. Sucrose, fructose and glucose presence in this study is related to cell signaling. Thus, hormonal signals and carbohydrates alter metabolism, triggering PLBs initiation and development in C. tigrina.